1967
DOI: 10.1161/01.res.21.4.525
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Studying Isolated Resistance Vessels from Rabbit Mesentery and Brain and Their Responses to Drugs

Abstract: A technique has been developed for studying the reactivity of single, isolated resistance vessels, 50 to 250 µ o.d., perfused at constant flow rate. The validity of the method is established because responses to a given stimulating agent are reproducible and stable over a reasonable period of time. The magnitude of the response is dependent on the perfusion pressure, being maximal at a physiological pressure level. Resistance vessels from mesentery and brain of normal rabbits were compared with respect to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…Although a number of investigators have shown that isolated preparations of cerebral blood vessels respond to vasoactive substances, 12 " 16 the contraction of these vessels to neurogenic transmitter in vitro has not been unequivocally demonstrated. Nielsen et al 3 have shown that tyramine will induce a dose-related 336 (12) 29 (7) BEVAN, BEVAN response in the isolated middle cerebral artery of the cat, and that this effect, in part at any rate, is dependent upon the release of adrenergic transmitter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of investigators have shown that isolated preparations of cerebral blood vessels respond to vasoactive substances, 12 " 16 the contraction of these vessels to neurogenic transmitter in vitro has not been unequivocally demonstrated. Nielsen et al 3 have shown that tyramine will induce a dose-related 336 (12) 29 (7) BEVAN, BEVAN response in the isolated middle cerebral artery of the cat, and that this effect, in part at any rate, is dependent upon the release of adrenergic transmitter.…”
Section: Discussionmentioning
confidence: 99%
“…10 These findings are consistent with observations that the adrenergic innervation of the basilar artery in the rabbit is similar in position and density to that seen in many other arteries, 4 -18 but that the transmitter threshold is higher in cerebral vessels than in other regions. 12 The basis of the difference in reactivity to sympathetic neural influence of the caudal basilar and the ear artery, and between the caudal basilar and the vertebral and distal basilar, is not known. Our observations show that differences in the number of muscle cell layers in the vessel wall do not form the basis of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also are consistent with the results of three in vitro studies. Uchida and his colleagues 16 found that cerebral arteries 50 to 250 y. in diameter displayed weak vasoconstrictor responses to large concentrations of norepinephrine. Similarly, Nielsen and Owman 17 and Toda and Fujita 18 found that strips from large cerebral arteries showed relatively weak contractile responses to norepinephrine.…”
Section: 7mentioning
confidence: 98%
“…Thus, various devices for the recording of contractile activity of cylindrical segments perfused intra-and extraluminally have been reported. For instance, a large (0.5 mm or more outer diameter) artery, or a much smaller one was isolated and perfused with solution at a constant pressure or flow volume ; and 1) the change in isometric tension can be measured by passing two wire hooks through the vessel wall, and connecting them to a strain gauge (Cohen et al 1984) ; 2) the external vessel diameter can be recorded by means of a photoelectric (Sakaguchi et al 1979;Schabert et al 1980) or an ultrasonic device (Angus et al 1983) ; 3) the change in perfusion pressure at the proximal site can be measured (Uchida et al 1967) ; 4) Teflon® (Lusamvuku et al 1980) or stainless steel (Hongo and Chiba 1983) tubing can be inserted into the lumen and be connected to a perfusion circuit, which acts as a series resistance.…”
Section: Discussionmentioning
confidence: 99%